Distribution of 90Sr in the High Seas and Coastal Regions of Korea-Japan-Russia-China - Muslim Muslim (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2006)
Distribusi 90Sr di daerah laut lepas dan pantai Korea-Jepang-Rusia-China telah diteliti sejak 30 Juni sampai 2 Agustus 2000. Pengambilan sampel permukaan air laut dilakukan di Laut China Timur, Laut Jepang (LautTimur), Laut Okhotsk dan Barat laut Samudera Pacific. Salinitas, temperatur dan konsentrasi 90Sr bervariasi dan tidak menunjukkan saling berhubungan. Temperatur lebih didominasi oleh pengaruh posisi lintang. Konsentrasi 90Sr banyak dipengaruhi oleh beberapa faktor seperti sumber limbah buangan radioaktif dan faktor fisika. Dilaut Jepang distribusi konsentrasi 90Sr lebih didominasi oleh pengaruh jarak dari tempat sumber pembuangan limbah radioaktif, tetapi di lokasi-lokasi lain dipengaruhi oleh faktor kondisi fisik.Kata kunci: 90Sr, laut lepas, daerah pantai, faktor fisika.Distribution of 90Sr in the high seas and coastal regions of Korea-Japan-Russia-China have been measured from 30 June 2000 to 2 August 2000. The surface seawaters were collected from East China Sea, Japan Sea (East Sea), Okhotsk Sea and Northwest Pacific Ocean. Salinity, temperature and 90Sr concentration were variable, and did not show correlation each others. The temperature levels dominantly influenced by latitude effect position. The 90Sr activities ranged from not detectable to 2.22 mBq/l (mean: 1.18, n:23). The distribution of 90Sr concentrations were more uniform in the coastal regions than in the high seas regions. The concentration of 90Sr in this study area were caused by some factors such as from source radioactive waste discharge and physical factors condition. The distribution 90Sr in Japan Sea generally was influenced by distance factor from radioactive waste discharge, but the other locations were influenced by physical factors condition.Key words: 90Sr, high seas, coastal regions, physical factors.